Downward wage rigidity and automatic wage indexation: evidence from monthly micro wage data - Patrick Lünnemann; Ladislav Wintr (European Central Bank (ECB), 2010)
This paper assesses the degree of downward wage rigidity in Luxembourg using an administrative monthly data set on individual wages covering the entire economy over the period from January 2001 to January 2007. After limiting for measurement error, which would otherwise bias downwards the estimates of wage rigidity, we conclude that nearly all workers in Luxembourg are potentially subject to downward real wage rigidity. Our results are robust to different procedures to adjust for measurement error and methods for estimation of downward wage rigidity. We report relatively small differences in the frequency of nominal wage cuts across occupational groups and sectors. In addition, the observed rigidity does not seem to be driven predominantly by the absence of negative shocks. We show that the real wage rigidity is related to the automatic wage indexation, while additional factors might be necessary to explain the high degree of downward wage rigidity.
Keywords: J31; 330; downward wage rigidity; wage indexation; Lohnrigidität; Lohnindexierung